English Teaching Techniques Used by the Sixth Semester Students of DEE UMS in Microteaching Class - SRI UTAMI, MELATI, Agus Wijayanto, Ph. D (2017)
This research was a descriptive qualitative study aimed to classify the types of English teaching used by the sixth semester students of DEE UMS in microteaching class and to investigate whether the trainees vary their teaching techniques in relation to different teaching materials. The data of this research were 20 video of the thirteen teacher trainees which is transcribed into the written form. The result of the study was that the writer has found fifteen types of English teaching techniques used by the teacher trainees, i.e Grammar activity, Reading comprehension activity, Reading aloud, Getting students to self-correct, Listening practice, Builiding up to a new model, Substitution drilling, Correction, Repetition, Authentic materials, Language games, GBI cycle, Inquiry cycle, and Language focus. Almost all of teacher trainees combined one until three teaching techniques to deliver some types of teaching materials. The trainees were also combined the technique by using media such as application and audio recorder.